Metabolite profiling and transcriptome analyses provide insight into the regulatory network of graft incompatibility in litchi - Hou, Yanjie; Qin, Xianquan; Qiu, Hongye; Li, Dongbo; Xu, Ning; Zhang, Shuwei; Fang, Chen; Li, Hongli (Frontiers in Genetics, 2023)
Litchi is an important commercial fruit crop widely grown in the world. Graft incompatibility between rootstocks and scions is a major constraint for large-scale cultivation of litchi orchards, popularization of new and excellent litchi varieties, and associated industrial development. Further, the genetic mechanism of graft incompatibility is still unclear in litchi. To reduce the incompatibility problems, this study investigated metabolic and transcriptomic differences between graft compatible and incompatible rootstock-scion combinations of litchi. The result of metabolomics analysis showed that incompatible rootstock-scion interaction modified the profiles of several metabolic substances. However, various compounds of flavonoids, phenolic acids, and lignin predominantly exhibited significantly altered abundance in graft incompatible combinations. Transcriptome analysis identified that graft incompatibility induces dynamic gene differences. The majority of these differentially expressed genes were enriched in biosynthetic pathways of phenylpropanoids. The differential expressions of genes in these pathways could be linked to the differential abundance levels of flavonoids, phenolic acids, and lignin compounds. Integrated metabolomic and transcriptomic analyses revealed a strong relationship between differential genes and differential metabolites identified in this study. In addition, identified hub genes and metabolites were closely associated with graft incompatibility of litchi. This study characterized the abundance of metabolites and genes in graft incompatible combinations and further discussed the genetic mechanism of graft incompatibility in litchi. Our results provide a platform to dissect the molecular mechanisms of graft incompatibility in the litchi fruit.